OIL HEAT TREATMENT EFFECTS ON COLOR CHANGES IN JABON AND SENGON WOODS - Intan Fajar Suri; Irvan Seprianta; Syifaulafifah; Galang Adandi Aman; Monika Theresia Simarmata (Jurnal Belantara, 2026)
The increasing demand for wood resources has encouraged the utilization of fast-growing species such as jabon (Neolamarckia cadamba) and sengon (Falcataria moluccana), although their relatively low-quality limits their application in high-value products. This study evaluated the effect of oil heat treatment (OHT) on the color characteristics of both species and examined consumer preferences toward the resulting wood appearance. Wood samples were treated in palm oil at temperatures of 170°C, 190°C, and 210°C for 2 h. Color changes were assessed using the CIE-Lab system, and a preference survey with 100 respondents was conducted to evaluate visual acceptance. The results showed that increasing treatment temperature progressively reduced the lightness (L*) values of both species, producing darker wood surfaces. Sengon exhibited a greater degree of darkening than jabon, indicating different responses to thermal modification. Changes in the a* and b* parameters also varied between species, reflecting differences in their chemical and anatomical characteristics. The darker, more uniform colors achieved after treatment enhanced the visual appearance of both woods. Consumer responses indicated that moderately dark colors were generally preferred, with jabon treated at 190°C and sengon treated at 210°C receiving the highest appreciation. These findings suggest that oil heat treatment is a promising, environmentally friendly approach to improving the aesthetic value and market potential of fast-growing wood species. Future studies should investigate the effects of OHT on the physical, mechanical, and durability properties of modified wood.